Advancing recovery and cryopreservation of rat spermatogonia for germ stem cell banking - Syvyk, T.L.; Djachenko, L.S.; Syvyk, A.E. (Вiopolymers and Cell, 2018)
Aim. Optimisation of spermatogonial cryopreservation medium and spermatogonia recovery procedures essential for the male germ cell research and spermatogonia mediated transgenesis in rodents. Methods. PCR, LIVE/DEAD® Cell Viability Assays, Spermatogonial Colony Forming Assay, immunocytochemistry, cryopreservation and thawing spermatogonia cells. Results. Three Sleeping Beauty mutant spermatogonia stem cell lines were stored in liquid nitrogen, after 17–24 months of cryopreservation, were derived in parallel from recovered cryopreserved cultures via an established laminin selection procedure and by an alternative method termed as direct SG (Spermatogonia Growth) medium selection on MEFs (mouse embrionic fibroblasts). A spermatogenic potential of the cell lines derived by these two methods was verified by the spermatogonia transplantation in vivo and reestablishing the mutant animal lines. We optimized the concentration of DMSO in a freezing medium for spermatogonial cell lines. Conclusions. We developed and optimized recovery of spermatogonial stem cells, that could be consistently derived from the freshly thawed stocks of testicular cells cryopreserved in SG medium. Our data suggest that the 8% DMSO is the most effective concentration of the cryoprotectant in SG medium. Мета. Оптимізувати кріоконсервуючий розчин для сперматогонії і процедуру її відновлення. Методи. ПЛР, Тест на виживання клітин, Тест на формування сперматогональних колоний, імуноцитохімія, кріоконсервація и розморожування сперматогонії. Результати. Три мутовані сперматогональні стовбурові клітинні лінії Спляча Красуня після 17–24 місяців кріоконсервації були відновлені двома методами: традиційним – із застосуванням ламінінової селекції і новим методом селекції ССК у живильному середовищі на мишачих ембріональних фібробластах. Мутовані лінії ССК, відновлені двома методами, трансплантували у сім'яники самців-реципиєнтів. Були отримані трансгенні нащадки. Ми вдосконалили концентрацію ДМСО в розчині для заморожування ліній ССК. Висновки. Після виділення ССК із сім'янників щура і тривалого кріозбереження, оптимізована процедура відновлення їх у живильному середовищі дозволяє успішно отримувати трансгенні тварини із банку мутованих ліній ССК. Результати доводять доцільність включення 8 % ДМСО до складу живильного середовища для ССК з метою кріоконсервування. Цель. Оптимизировать раствор для криоконсервации сперматогонии и процедуру её восстановления. Методы. ПЦР, Тест на выживаемость клеток, Тест на формирование сперматогональных колоний, иммуноцитохимия, криоконсервация и размораживание сперматогонии. Результаты. Три мутированных сперматогональных стволовых клеточных линий Спящая Красавица после 17–24 месяцев криоконсервации были восстановлены двумя методами: традиционным – с применением ламининовой селекции и новым методом селекции сперматогональных стволовых клеток (ССК) в питательной среде на мышиных эмбриональных фибробластах. Мутированные линии ССК, восстановленные двумя способами, трансплантировали в семяники самцов-реципиентов. Было получено трансгенное потомство. Мы усовершенствовали концентрацию диметилсульфоксида (ДМСО) в растворе для замораживания линий ССК. Выводы. После виделения ССК из семяников крыс и длительного криосохранения, оптимизированная процедура востановления их в питательной среде позволяет успешно получать трансгенных животных из банка мутированных линий ССК. Наши результаты доказывают целесообразность включения 8 % ДМСО в состав питательной среды для ССК с целью криоконсервации.